Restorative justice, forgiveness and reparation for the victims - Fernandez-Manzano, Maria Lourdes (Oñati Socio-Legal Series, 2014)
Forgiveness is not one of the aims of restorative processes. However, the conditions that enable these processes can also make forgiveness more likely. The positive impact that forgiveness can have on the lives of the victims of serious crimes, such as terrorism, means that this issue should be discussed when seeking to apply restorative justice in any situation. The main philosophies of forgiveness, the absence of pressure to forgive and the consequences of interpersonal forgiveness in social reconciliation are among the questions addressed.